2007
DOI: 10.1021/np0703996
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactones from the Roots of Ferula varia and Their Cytotoxic Activity

Abstract: The ethyl acetate-soluble fraction from a MeOH extract of the roots of Ferula varia gave six new sesquiterpene lactones (1-6) and five known sesquiterpenes (7-11). Their structures were established on the basis of spectroscopic evidence. The cytotoxic activities of 1-11 were evaluated against selected human cancer cell lines. Compound 4 showed significant selective cytotoxicity against multidrug-resistant cancer cells (KB-C2). The cytotoxicities of compounds 1, 3, 5, 8, and 11 against KB-C2 cells were enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…The 1 H-and 13 C-NMR spectra showed the signals due to two tert-methyl groups, two vinyl methyl groups, two methylenes, two methines, four oxygen-bearing methines, one quaternary carbon, one oxygen-bearing quaternary carbon, one exo-methylene, one sp 2 methine, two sp 2 quaternary carbons, two carbonyl carbons, and a glucosyl moiety. The data for the aglycone moiety were similar to those of a eudesmane-type sesquiterpene lactone with an angeloyl group (1β-angeloyloxy-11β-hydroxy-5βH,6αH,7αH,10α-methyleudesm-2(3),5(15)-diene-6,12-olide, I) previously isolated from the EtOAc-soluble fraction of this plant, 3) except for the observation of the signals due to two additional oxygenbearing methines and a sugar moiety, as well as the absence of a disubstituted olefinic signal. The existence of the eudesmane-type sesquiterpene lactone structure with three oxygen-bearing functions and an angeloyl group was also supported by 2D-NMR spectral analysis.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The 1 H-and 13 C-NMR spectra showed the signals due to two tert-methyl groups, two vinyl methyl groups, two methylenes, two methines, four oxygen-bearing methines, one quaternary carbon, one oxygen-bearing quaternary carbon, one exo-methylene, one sp 2 methine, two sp 2 quaternary carbons, two carbonyl carbons, and a glucosyl moiety. The data for the aglycone moiety were similar to those of a eudesmane-type sesquiterpene lactone with an angeloyl group (1β-angeloyloxy-11β-hydroxy-5βH,6αH,7αH,10α-methyleudesm-2(3),5(15)-diene-6,12-olide, I) previously isolated from the EtOAc-soluble fraction of this plant, 3) except for the observation of the signals due to two additional oxygenbearing methines and a sugar moiety, as well as the absence of a disubstituted olefinic signal. The existence of the eudesmane-type sesquiterpene lactone structure with three oxygen-bearing functions and an angeloyl group was also supported by 2D-NMR spectral analysis.…”
supporting
confidence: 73%
“…The molecular formula of 6 was established as C 26 H 38 O 13 by HR-ESI-MS. The 1 H and 13 C NMR spectra were correlated with those of I, 3) except for the observation of signals due to two sugar moieties and the absence of signals arising from an angeloyl group. The two sugar moieties were confirmed as glucose and apiose by acid hydrolysis of 6.…”
mentioning
confidence: 96%
“…We have been investigating the herbal medicines of Uzbekistan with the aim of searching for novel drug leads (Umbelliferae [1][2][3][4][5][6][7][8][9][10], Compositae [11][12][13][14], Guttiferae [15,16], Polygonaceae [17], Cupressaceae [18], Paeoniaceae [19]). The aerial parts of Mediasia macrophylla (Umbelliferae) have been used traditionally as a perfume; an appetite enhancer; a natural preservative; and for treatment of rheumatism, nephritis, eczema, herpes, and injury [20].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Recent pharmacological research has demonstrated that different extracts of Ferula species contain sesquiterpene derivatives that have in particular proven to be cytotoxic on several cancer cell lines. 2,12 In addition, the extracts have been reported to have antimicrobial, anthelmintic, anticonvulsant, antispasmodic, antihyperglycemic, antihyperlipidemic, and antioxidant activities. [13][14][15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%